ANTIMICROBIAL EFFECTS OF THREE TROPICAL PLANT EXTRACTS ON STAPHYLOCOCCUS AUREUS, ESCHERICHIA COLI AND CANDIDA ALBICANS - Okigbo, R. N.; Mmeka, E. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Antimicrobial activities of the leaf extracts of Cymbopogon citatrus (lemongrass) and Vernonia amygdalina(bitter leaf ) and the seed extracts of Garcinia kola (bitter kola) were carried out. G. kola had effect only on Staphyococcus aureus and Escherıchıa coli with no inhibition on Candida albicans. Ethanol, cold water and hot water extracts of Vernonia amygdalina and Cymbopogon citratus showed inhibition on the three organism but G. kola ethanol, cold water and hot water extracts only inhibited S. aureus and E. coli with no inhibition on Candida albicans. The organism’s susceptibility varied with more inhibition to S. aureus and least to Candida albicans.